2018
DOI: 10.1029/2017ja025087
|View full text |Cite
|
Sign up to set email alerts
|

Van Allen Probes Observations of Drift‐Bounce Resonance and Energy Transfer Between Energetic Ring Current Protons and Poloidal Pc4 Wave

Abstract: A poloidal Pc4 wave and proton flux oscillations are observed in the inner magnetosphere on the dayside near the magnetic equator by the Van Allen Probes spacecraft on 2 March 2014. The flux oscillations are observed in the energy range of 67.0 to 268.8 keV with the same frequency of the poloidal Pc4 wave. We find pitch angle and energy dispersion in the phase difference between the poloidal magnetic field and the proton flux oscillations, which are features of drift-bounce resonance. We estimate the resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Proton fluxes with conjugate pitch angles ( α , 180°− α ) show out‐of‐phase oscillations. This is a typical feature of the pitch angle distributions in the drift‐bounce resonance of P2 waves (e.g., Oimatsu et al, ; Takahashi et al, ). Figure c shows PSD of B ν and Δ f H+ .…”
Section: Measurementsmentioning
confidence: 87%
See 2 more Smart Citations
“…Proton fluxes with conjugate pitch angles ( α , 180°− α ) show out‐of‐phase oscillations. This is a typical feature of the pitch angle distributions in the drift‐bounce resonance of P2 waves (e.g., Oimatsu et al, ; Takahashi et al, ). Figure c shows PSD of B ν and Δ f H+ .…”
Section: Measurementsmentioning
confidence: 87%
“…The poloidal ultralow frequency (ULF) wave is one of the most prominent waves in the inner magnetosphere and at the geosynchronous orbit. Studies have shown that the poloidal Pc 4–5 (a frequency range of 1.67–22.2 mHz) waves are excited through drift/drift‐bounce resonance with ~100 keV protons (Dai et al, ; Min et al, ; Oimatsu et al, ; Takahashi et al, ) or bounce resonance of ~10 keV protons (Hughes et al, ; Liu et al, ; Takahashi et al, ). These waves are notable because they can also resonate with and modify inner magnetospheric electron populations (Claudepierre et al, ; Hao et al, ; Mann et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass-dependent acceleration may be possible in the plasma sheet with magnetic and electric field perturbations (e.g., Catapano et al, 2016), in the reconnection region and around the separatrix between closed and open magnetic fields (where the Hall electric field exists; Liang et al, 2017), around a dipolarization front (i.e., a reconnection jet front) where the magnetic field increases in less than seconds and a strong electric field is thus induced (Runov et al, 2015), near the transition region from the stretched magnetic field to the dipole-like field where a fast flow associated with reconnection slows down and the electric field is induced by the magnetic field pileup (Nakayama et al, 2016). Possible waves are dispersive Alfvén waves (e.g., Chaston et al, 2016), which can accelerate O+ that are simultaneously extracted from the topside ionosphere and/or preexist on the same field lines; waves/fluctuations with a frequency range of electron-ion cyclotron waves (e.g., Nosé et al, 2014); and ULF waves (e.g., Mitani et al, 2018;Oimatsu et al, 2018), which can resonate with drifting and bouncing ring current ions. However, as higher-energy O+ are more difficult to transport to the inner magnetosphere, it is still a controversial issue whether a large number of those accelerated O+ can penetrate to around/inside geosynchronous orbit.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…ω b and ω d in a dipole magnetic field are provided as ω b = normalπ2W/mi2LRET)(sinαE and ω d = − 6italicWLP)(sinαEqBERE2 + 2ψ0L3sinφBERE2 + Ω E , where m i is the ion mass, R E is the Earth's radius, α E is the pitch angle at the geomagnetic equator, B E is the equatorial magnetic field at the surface of the Earth, q is the electric charge, φ is the eastward angle from the midnight, Ω E is the angular frequency of the corotation of the Earth, and ψ 0 is the electric potential of the convection electric field obtained from the Volland‐Stern model (Maynard & Chen, ; Stern, ; Volland, ). We also utilized the following equations: T (sin α E ) = 1.351 − 0.925sin α E + 0.558sin 2 α E − 0.248sin 3 α E and P (sin α E ) = 0.340 + 0.226sin α E − 0.154sin 2 α E + 0.088sin 3 α E (Hamlin et al, ; Oimatsu, Nosé, Takahashi, et al, ; Yang, Zong, Fu, Li, et al, ).…”
Section: Case Study Of the 17 February 2016 Eventmentioning
confidence: 99%